Demographic and Clinical Profile in Patients with Cirrhosis of Liver - Sharma, Pasanda; Baral, Shankar; Poudel, Sujan Chandra; Tiwari, Ashok; Gyawali, Merina; Bhattarai, Subash (Journal of College of Medical Sciences-Nepal, 2025)
Background Liver cirrhosis is a common problem in Nepal. Different causes and factors are responsible for cirrhosis and its progression. This study was undertaken to study the demographic and clinical profiles of patients with liver cirrhosis attending a tertiary care hospital in Gandaki province of Nepal. Methods Four hundred patients with liver cirrhosis attended to the hospital. Their demographic, clinical profile and endoscopic findings were studied. Ethical approval was taken from Institutional Review Committee of Manipal College of Medical Sciences. SPSS version 16 was used for statistical analysis. Results The mean age of patients was 57±10.72 years ranging from 29-75 years of age with male predominance (M: F=2:1). The study found farmers to be most commonly affected followed by retired personnels and those living in rural areas. All castes and ethnicity were affected but the most common were Mongols (37.5%), Dalit (33.5%) Chhetri/Brahmins (22.5%), followed by Newars (10.6%). Alcohol was the most common aetiology of cirrhosis occurring in 360(90%) patients. Low socioeconomic status highly contributed to chronic alcohol consumption. The most common presentation was abdominal distension followed by anorexia, fatigue, vomiting. Ascites was present in 256(64%) patients and 146(36.5%) patients had upper gastrointestinal bleed as their presentation to the hospital. The most common cause of mortality was rebleeding occurring in 13(40%) followed by hepatic encephalopathy in 7(22%) and hepatorenal syndrome in 6(19%) patients. Conclusions Patients present in hospital with varied signs, symptoms and complications of liver cirrhosis. Educating about the adverse effects of alcohol and tight regulations may help in early detection and management of alcoholic liver diseases which might reduce morbidity and mortality of liver cirrhosis in Nepal especially in rural areas.